Comparative Study of Various Immune Parameters in Three Bivalve Species during a Natural Bloom of Dinophysis acuminata in Santa Catarina Island, Brazil - Danielle Ferraz Mello; Luis Antonio de Oliveira Proença; Margherita Anna Barracco (Toxins, 2010)
This study aimed to verify if Dinophysis acuminata natural blooms affected the immune system of three bivalves: the oyster, Crassostrea gigas, the mussel, Perna perna, and the clam, Anomalocardia brasiliana. Animals were obtained from a renowned mariculture farm in the southern bay of Santa Catarina Island during, and 30 days after (controls), an algal bloom. Various immunological parameters were assessed in the hemolymph of the animals: total and differential hemocyte counts, percentage of apoptotic hemocytes, protein concentration, hemagglutinating titer and phenoloxidase activity. The results showed that the mussel was the most affected species, with several altered immune parameters, whereas the immunological profile of clams and oysters was partially and completely unaffected, respectively.